Pengembangan Gim “FloNa Savior” untuk Edukasi Konservasi Tumbuhan dan Satwa Dilindungi Berbasis Realitas Tertambah - Ricky Yohanes; Paramaresthi Windriyani (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
The purpose of this research is to develop an educational game about conservation protected plants and animals using augmented reality technologies. This game was developed as an alternative learning media to obtain education regarding importance of conversation protected plants and animals. This research uses Game Development Life Cycle (GDLC) method. The method itself consists of six stages, starting from initiation, pre-production, production, testing, beta and release. The final result of this research is an educational game titled "FloNa Savior", it can be played on an ARCore compatible Android device. Based on the beta testing, from 24 respondents, 100% of respondent become more understand about importance of conservation protected plants and animals after playing "FloNa Savior" and 70.8% respondents stated that the augmented reality feature can help them to understand more about educational content.